Quantum-enhanced photoprotection in neuroprotein architectures emerges from collective light-matter interactions - Patwa, Hamza; Babcock, Nathan S.; Kurian, Philip (Frontiers in Physics, 2024)
Background: Superradiance is the phenomenon of many identical quantum systems absorbing and/or emitting photons collectively at a higher rate than any one system can individually. This phenomenon was first observed in gases and crystal lattices but has more recently been studied in idealized distributions of two-level systems (TLSs) and in realistic photosynthetic nanotubes and cytoskeletal architectures. Methods: Superradiant effects are studied here in idealized toy model systems and realistic biological mega-networks of tryptophan (Trp) molecules, which are strongly fluorescent amino acids found in many proteins. Each Trp molecule acts as a chromophore absorbing in the ultraviolet spectrum and can be treated as a TLS with its 1L_a excited singlet state. We use a non-Hermitian Hamiltonian to describe interactions of the Trp chromophore network with the electromagnetic field. We numerically diagonalize the Hamiltonian to obtain its complex eigenvalues, where the real part is the collective energy and the imaginary part is the associated enhancement rate. We also consider multiple realizations of increasing static disorder in either the site energies or the single-Trp decay rates. Results: We obtained the energies, enhancement rates, and quantum yields for realistic microtubules, actin filament bundles, and amyloid fibrils of differing lengths. We find that all structures exhibit highly superradiant states near the low-energy portion of the spectrum, which enhances the magnitude and robustness of the quantum yield to static disorder and thermal noise. Conclusions: The high quantum yield and stable superradiant states in these biological architectures may play a photoprotective role in vivo, downconverting energetic ultraviolet photons emitted from reactive free radical species to longer, safer wavelengths and thereby mitigating biochemical stress and photophysical damage. Contrary to conventional assumptions that quantum effects cannot survive in biosystems at high temperatures, our results suggest that macropolymers of TLSs in microtubules, actin filaments, and amyloid fibrils exhibit observable and robust quantum yield enhancements up to at least the micron scale. Superradiant enhancements and high quantum yields in neuroprotein polymers would thus play a crucial role in information processing in the brain, the development of neurodegenerative diseases such as Alzheimer's, and many other pathologies characterized by anomalous protein aggregates.